Hydrogen generation from aluminum hydride for wearable polymer electrolyte membrane fuel cells. (15th June 2016) - Thampan, T.; Atwater, T.; Cook, C.; Novoa, J.; Sutorik, A.C.
Abstract: Aluminum hydride (AlH3 ) has been identified as a promising H2 storage material for fuel cell systems and offers a significant weight savings over conventional Li-ion batteries, due its high H2 storage capacity and simple balance of plant requirements for H2 generation. This work reports on the development and characterization of a novel, wearable AlH3 based PEM fuel cell system. System characterization revealed an unexpectedly low energy density value, 25% lower than anticipated, (436 Wh kg −1 vs. 582 Wh kg −1 for 1440 Wh) due in part to a previously unpublished phenomenon of incomplete α-AlH3 thermolysis. Based on literature reports, complete thermolysis was expected to occur at <180 °C, however this work reports on conditions where the full H2 yield cannot be obtained despite high temperature (>250 °C) exposure. This work provides an experimental characterization of this phenomenon and quantitatively describes it by developing a new model in the framework of the Avrami–Erofeev phase transformation model, which can be utilized for the optimum design of high energy density AlH3 cartridges. Highlights: Development and characterization of a new, wearable AlH3 based PEM fuel cell system. Characterization of partial vs. complete AlH3 dehydrogenation phenomenon. Novel kinetic model developed & verified to predict AlH3 dehydrogenation phenomenon. Model and experimental characterization can be utilized to develop improved systems.